The Role of General and Selective Task Instructions on Students’ Processing of Multiple Conflicting Documents - Cerdán, Raquel; Marín, Maria del Carmen (Frontiers in Psychology, 2019)
This study was designed to test the role of general and selective task instructions when processing documents, which vary as regards trustworthiness and position towards a conflicting topic. With selective task instructions we referred to concrete guidelines as how to read the texts and how to select appropriate documents and contents, in contrast to general task instructions. Students were presented with four different conflicting documents in an electronic learning environment and were told to write an essay based on the information from the texts. Only half of the students were told to only use information from two out of the four texts to write their essay (i.e., selective condition). As predicted, students told to focus on specific documents and not use all of them for the assigned task (i.e. selective condition) better discriminated the quality of documents and type of information for the task.